Spontaneous neonatal renal vein thromboses: Should we treat them all? A report of five cases and a literature review - François Niada; René Tabin; Simon Kayemba-Kay's (Elsevier, 2018)
Renal vein thrombosis (RVT) is a rare but well-known neonatal entity for which several therapeutic modalities are reported in the literature because of the lack of consensus management guidelines. A retrospective study of the medical records of children managed between January 1990 and December 2013, and whose final diagnosis was RVT. The diagnosis was initially clinical and subsequently confirmed by the abdominal ultrasonography (AUS) and Doppler imaging if necessary. The abdominal CT scan was performed when the AUS finding led to the suspicion of RVT extension to the inferior vena cava (IVC). Each patient's birth parameters (birth weight [BW], birth length [BL], and head circumference [HC]) and modalities were recorded. The treatment modalities, the outcome at follow-up along with results of etiological screening were also recorded. Results: Five newborn infants were diagnosed as having unilateral RVT at the mean postnatal age of 3.8 days (range, 1-11 days). All presented with a classical triad associated nephromegaly, thrombocytopenia, and gross hematuria. Two patients had genetic thrombophilic risk factors (1 heterozygous Leiden factor V mutation in case 4, and Activated Protein C resistance in case 5). Two infants were managed conservatively, and the other three received antithrombotic treatment (recombinant tissue plasminogen activator and heparin). All five patients had a similar course, leading to non-functioning renal atrophy, despite aggressive thrombolytic therapy or conservative treatment. Conclusion: We suggest that simple unilateral RVT be managed conservatively, while antithrombotic therapy may be attempted for unilateral RVT extending into the inferior vena cava and for bilateral RVT.